2021
DOI: 10.1136/jnnp-2020-325278
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral staged magnetic resonance-guided focused ultrasound thalamotomy for the treatment of essential tremor: a case series study

Abstract: BackgroundUnilateral magnetic resonance-guided focused ultrasound (FUS) thalamotomy is efficacious for the treatment of medically refractory essential tremor (ET). Viability of bilateral FUS ablation is unexplored.MethodsPatients diagnosed with medically refractory ET and previously treated with unilateral FUS thalamotomy at least 5 months before underwent bilateral treatment. The timepoints were baseline (before first thalamotomy) and FUS1 and FUS2 (4 weeks before and 6 months after second thalamotomy, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 9 publications
3
20
0
1
Order By: Relevance
“…A recent retrospective series of 9 patients who underwent bilateral MRgFUS thalamotomies at 2 centers was recently published and suggested the intervention might be safe 29 . We report here the first prospective study of bilateral thalamotomies.…”
Section: Discussionmentioning
confidence: 86%
“…A recent retrospective series of 9 patients who underwent bilateral MRgFUS thalamotomies at 2 centers was recently published and suggested the intervention might be safe 29 . We report here the first prospective study of bilateral thalamotomies.…”
Section: Discussionmentioning
confidence: 86%
“…The recent publications by Martínez‐Fernández et al, 1 Iorio‐Morin et al, 2 and Fukutome et al 3 reported encouraging results after staged bilateral MRgHiFUS thalamotomy in essential tremor patients. These observations indicate that staged bilateral ablations with MRgHiFUS might be possible and safe.…”
Section: Discussionmentioning
confidence: 95%
“…However, majority of the available data for bilateral thalamotomy were published from the 1960s to 1980s when MRI and CT were not generally available to plan and confirm the ablative targets. Recent studies of bilateral thalamotomy indicated that dysarthria was mild or transient (19)(20)(21)(22)(23)(24). Nevertheless, the second thalamotomy should be carefully considered, and for a safe second thalamotomy, it is recommended to verify the absence of adverse events associated with the first thalamotomy, keep the longest possible interval between the first and second surgery (at least 12 moths), include patients aged less than 70 years, and ensure the smallest possible lesion volume.…”
Section: Discussionmentioning
confidence: 99%